Sustainability of migratory pastoralism through value addition during Covid-19 pandemic in Kachchh district - KUMAR, DINESH; DASHORA, KAVYA; SINGH, SURYA PRAKASH; KUMAR, VIVEK; NAIK, S N; JANI, HITESH; PORWAL, VIKRAM KAPALI (The Indian Journal of Animal Sciences, 2022)
This study was conducted among the Maldhari community to understand the sustainability of migratory pastoralism during Covid-19. Bhuj and Lakpat Talukas of Kachchh district, Gujarat were selected to study the effect of profile variables on the annual income and net income of the families. The study revealed that family size and taluka were the significant factors influencing total income whereas taluka was the only significant factor influencing net income. Due to reduced sale of milk resulting from Covid-19, most of the milk was converted i to khoa and the income generated from its sale was the major source of income for the migratory families. Cow dung fetched a minimal price which served as major source of their livelihood with no input cost. The value addition with better marketing facilities can significantly enhance the income of the pastoralists in the Kachchh district.